Washings and cryoprotectants for the production of Tilapia Surimi - de Oliveira, Dayse Lícia [UNESP]; Grassi, Thiago Luís Magnani [UNESP]; Santo, Edson Francisco Do Espirito; Cavazzana, Jefferson Felipe [UNESP]; Marcos, Marcelo Tacconi De Siqueira [UNESP]; Ponsano, Elisa Helena Giglio [UNESP] (FapUNIFESP (SciELO), 2017)
This research aimed at studying the effects of different washing conditions (distilled water x distilled water + NaHCO3 + NaCl) and cryoprotectants (NaCl + saccharose x sorbitol + sodium tripolyphosphate) for the production of tilapia surimi. The experiment used a factorial design 2 x 2 and the variables analyzed were proximate composition, non-nitrogen protein (NNP) removal, texture, color and yield. The protein and moisture contents of the surimi were influenced neither by washings nor by cryoprotectants, while the ash content was higher when NaCl + saccharose were used as the cryoprotectants and the yield was higher when only distilled water was used for the washings. Combining distilled water for the washings and NaCl + saccharose as the cryoprotectants provided the highest lipid and NNP removals. The different treatments produced surimi gels with similar colors and texture.
Keywords: Color; Fish; Proteins; Texture